Q. 115.0( 1 Vote )
3x 2 – 2x – 1= 0
Let x = 1
⇒ 3(1) 2 – 2(1)– 1 = 3 – 2 – 1 = 0.
Therefore, the given value of x is a solution of the given equation.
Rate this question :
How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Introduction to Linear Equations in Two Variables62 mins
Pair of Linear Equations-Yahaan se laye marks57 mins
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
view all courses
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
RELATED QUESTIONS :
Draw the graph ofNCERT - Mathematics